Modular nanotheranostic agents for protistan parasitic diseases: Magic bullets with tracers - Maciver, Sutherland Kester; Sumayah, Abdelnasir *; Ayaz, Anwar *; Siddiqui, Ruqaiyyah; Khan, Naveed Ahmed (Elsevier, 2023)
Protistan parasitic infections contribute significantly to morbidity and mortality, causing more than 2 billion human infections annually. However, current treatments are often limited; due to ineffective drugs and drug resistance, thus better options are urgently required. In the present context, theranostics agents are those that offer simultaneous detection, diagnosis and even treatment of protistan parasitic diseases. “Nanotheranostics” is the term used to describe such agents, that are around 100 nm or less in size. Anti-parasitic activity of nanoparticles (NPs) has been reported, and many have useful intrinsic imaging properties, but it is perhaps their multifunctional nature that offers the greatest potential. NPs may be used as adapters onto which various subunits with different functions may be attached. These subunits may facilitate targeting parasites, coupled with toxins to eradicate parasites, and probe subunits for detection of particles and/or parasites. The modular nature of nano-platforms promises a “mix and match” approach for the construction of tailored agents by using combinations of these subunits against different protistan parasites. Even though many of the subunits have shown promise alone, these have not yet been put together convincingly enough to form working theranostics against protistan parasites. Although the clinical application of nanotheranostics to protistan parasitic infections in humans requires more research, we conclude that they offer not just a realisation of Paul Ehrlich’s long imagined “magic bullet” concept, but potentially are magic bullets combined with tracer bullets.